New edition of classic text on bananas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Stover R.H., and N.W.Simmonds, 1988. Bananas. ISBN 0582 463 572